Consumer and sensory evaluation techniques how to sense successful products - Saint-Denis, Cecilia Y. 1972- (John Wiley & Sons, 2018)
Practical reference on the latest sensory and consumer evaluation techniques available to professionals and academics working in food and consumer goods product development and marketing. This unique manual describes how to implement specific sensory and consumer methods based on context and objective. Presented in a direct and straightforward language that will speak to the industry professionals and academics who are on the ground attempting to solve technical questions, it reviews, step by step, the various stages of a product evaluation. Included are practical examples from many industries that practitioners can relate to. The book also shows how to build a sustainable short-, medium-, and long-term product evaluation strategy, and guides readers on how to create customized methods, or even completely new approaches. Consumer and Sensory Evaluation Techniques speaks to management and decision-makers within organizations and addresses the main questions (eg: "How much will it cost?" and "How quickly can it be achieved?") that are faced when developing and testing new products before a launch. Chapters cover: the pillars of good consumer and sensory studies; sensory profile of a product: mapping internal sensory properties; the foundations of consumer evaluation; study plans and strategy—sustainable short, mid and long-term vision; real-life anticipation with market factors: concept, price, brand, market channel; and internal studies versus sub-contracting.--Provided by publisher.